2020
DOI: 10.1002/hyp.13759
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanistic causes of increased baseflow across northern Eurasia catchments underlain by permafrost

Abstract: Warming in the Arctic is occurring at twice the rate of the global average, resulting in permafrost thaw and a restructuring of the Arctic hydrologic cycle as indicated by increased stream discharge during low-flow periods. In these cold regions, permafrost thaw is postulated to increase low-flow discharge, or baseflow, through either:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Complete permafrost loss has the potential to influence subsurface fluxes and flowpaths at intermediate to basin-wide scales by altering the hydrogeologic framework that controls groundwater flow, groundwater storage, and hydrologic connectivity among inland waters, shallow groundwater, and deep sub-permafrost groundwater. Widespread increases in streamflow minimums and river baseflow across the Arcticboreal region suggest a multi-decadal shift from dominance of surface-water input toward increased groundwater input from a combination of connective supra-permafrost flow and sub-permafrost flow through open taliks (Smith et al, 2007;Walvoord and Striegl, 2007;Evans et al, 2020). This is consistent with the paradigm that proportionally more water is being recharged, stored, and circulated through deep subsurface pathways opened by extensive permafrost loss (Walvoord et al, 2012;Kurylyk and Walvoord, 2021).…”
Section: Response To Complete Permafrost Losssupporting
confidence: 69%
“…Complete permafrost loss has the potential to influence subsurface fluxes and flowpaths at intermediate to basin-wide scales by altering the hydrogeologic framework that controls groundwater flow, groundwater storage, and hydrologic connectivity among inland waters, shallow groundwater, and deep sub-permafrost groundwater. Widespread increases in streamflow minimums and river baseflow across the Arcticboreal region suggest a multi-decadal shift from dominance of surface-water input toward increased groundwater input from a combination of connective supra-permafrost flow and sub-permafrost flow through open taliks (Smith et al, 2007;Walvoord and Striegl, 2007;Evans et al, 2020). This is consistent with the paradigm that proportionally more water is being recharged, stored, and circulated through deep subsurface pathways opened by extensive permafrost loss (Walvoord et al, 2012;Kurylyk and Walvoord, 2021).…”
Section: Response To Complete Permafrost Losssupporting
confidence: 69%
“…Cross-correlation results demonstrated that lags between ∆ 13 C chronology and snowmelt season temperature and winter precipitation were 2 and 3 years, respectively (Table 3). Thawing permafrost and deepening active layer (the soil layer above the permafrost that thaws during the summer and refreezes during the winter) may raise, increasing soil filtration, deeper baseflow path, and increasing retention time, which strongly affect the catchment hydrology [97,98]. In our study area, the increases in baseflow are likely related to enhanced groundwater storage and winter groundwater discharge caused by permafrost thaw and are potentially also due to increased wet season rainfall.…”
Section: Potential Links Between Tree-ring Carbon Isotopes and Melting Seasonmentioning
confidence: 89%
“…These changes not only increase the available storage and flux of liquid groundwater, but also enhance the potential for exchange of water between aquifers and surface water bodies (blue lines, Fig. 1; Evans et al, 2020;Lemieux et al, 2020) and lead to shifts in vegetation (Christensen et al, 2004).…”
Section: Altered Surface Hydrologymentioning
confidence: 99%